2016
DOI: 10.1111/jop.12392
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cytoplasmic p27 in oral squamous cell carcinoma

Abstract: To the best of our knowledge, this is the first study to analyse cytoplasmic localization of p27 in OSCC and correlate with prognosis. Cytoplasmic localization is associated with poor prognosis in OSCC with lymph node metastasis allowing the consideration of cytoplasmic p27 in predicting prognosis and targeted therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…It has been stated that the loss of p27 expression can be one of the mechanisms leading to tumor development and progression (14,31,32). In many reports, alterations in the expression of p27 have been noticed (8,(13)(14)(15). Some researches of HNSCC have revealed decreased nuclear expression, of p27 which is comparable to our observations (2,(13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It has been stated that the loss of p27 expression can be one of the mechanisms leading to tumor development and progression (14,31,32). In many reports, alterations in the expression of p27 have been noticed (8,(13)(14)(15). Some researches of HNSCC have revealed decreased nuclear expression, of p27 which is comparable to our observations (2,(13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
“…In many reports, alterations in the expression of p27 have been noticed (8,(13)(14)(15). Some researches of HNSCC have revealed decreased nuclear expression, of p27 which is comparable to our observations (2,(13)(14)(15). Furthermore, Fillies et al In this study we also noticed reduced nuclear expression of p27 in cancer cells, which was weaker in comparison to papilloma cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cytoplasmic p27 is closely related to a poor prognosis in patients with tumour. Therefore, cytoplasmic p27 is considered an oncogenic protein [5][6][7][8][9]. Studies have shown that the serine/threonine protein kinase Akt protein is a key molecule that regulates the cytoplasmic p27 protein level; it can phosphorylate the threonine at position 157 of the p27 protein and restrict the cytoplasmic p27 protein to the nucleus [10].…”
Section: Introductionmentioning
confidence: 99%